Heat transfer and system performance of a novel solar ground-source heat-pump system with borehole heat exchangers using a combined parallel and series connection - Wu, Chunling; Song, Mengyao; Jin, Lu; Fu, Qiang; Zhu, Longhu (Frontiers in Energy Research, 2024)
A novel BHEs is proposed that can overcome the problems associated with the low heat-transfer efficiency of borehole heat-exchangers (BHEs) that are connected in series (BHEs-S) and the low heat-transfer temperature differences of BHEs that are connected in parallel (BHEs-P). The new BHE uses a combined series and parallel connection (BHEs-CSP), which can further be classified into individual in-series and in-parallel zones. A numerical model of the new BHEs-CSP is then developed to optimize the key design parameters such as borehole spacing, number of series stages, and heat-extraction methods. The results show that, with the optimal configuration, the average soil temperature with a BHEs-CSP is 6.70 °C higher than for a BHE that is connected in parallel. Furthermore, the heat-transfer efficiency can be improved by 4.1 % compared to BHEs that are connected in series. It is recommended that the distance between buried pipes in the series area and parallel area should be 5.25m, and the series number of buried pipe groups should be 4. To study the overall performance of the solar-assisted ground-source heat-pump with a BHEs-CSP (SAGSHP-CSP), a TRNSYS model is developed. The results show that the optimal area- and heat-storage-ratios (for in-series zone to in-parallel zone), using SAGSHP-CSP, are 1:4 and 3:2, respectively. Under these conditions, the system coefficient of performance (SCOP) is over 5.2 and the COP and SCOP is improved by 9.8 % and 13.0 % compared to GSHP systems with BHEs-P. Furthermore, an improvement by 18.4 % and 18.2 %, compared to the GSHP system with BHEs-S, is reported.